Transformasi The Park Mall Sebagai Ruang Publik Dan Implikasi Terhadap Pertarungan Kelas Di Kota Semarang - ANGGRAINI, LUSI RESTI (Program Studi Arsitektur, Fakultas Teknik dan Informatika, Universitas PGRI Semarang, 2024)
Public spaces as one of the elements reflecting the unique character of a society in achieving common goals. However, what happens if the space built as a public space is merely a discourse that does not realize the functions of a public space? The Park Mall Semarang serves as a space functioning as a public area, but due to social phenomena such as the emergence of new public spaces, The Park Mall has transformed into a discourse on public spaces, with implications for the class struggle among its visitors. This research is a preliminary study aimed at addressing the problem formulation related to the discourse of public spaces.This study uses a qualitative method with a grounded theory approach, collecting samples from the conditions of The Park Mall and the surrounding canal, as well as interviewing visitors in these two locations.The results indicate that the transformation of The Park Mall is influenced by different habitus, arenas, and cultural capital, which are closely related to class struggles where each group has its own objectives in advocating for their interests. Their ways of advocating involve articulating discourses that continuously nurture differences, which contributes to the class struggle.Thus, class struggle will always have implications for social changes, one of which is the transformation of The Park Mall, the subject of this research.